1978
DOI: 10.1093/nar/5.3.697
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of poly(A+) and poly(A) polysomal RNA in mouse liver and cultured mouse fibroblasts

Abstract: RNA excess hybridization experiments were used to measure the complexity of nuclear RNA, poly(A+) mRNA, poly(A-) mRNA, and EDTA-released polysomal RNA sedimenting at less than 80 S in mouse liver and in cultured mouse cells. With both cell types, poly(A-) RNA was found to contain 30-40% of the sequence diversity of total mRNA. In the case of liver this represents 5,700 poly(A-) molecules and 8,600 poly(A+) molecules for a total of approximately 14,300 different mRNAs. Comparison of the complexity of mRNA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
2

Year Published

1979
1979
1986
1986

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 28 publications
0
11
2
Order By: Relevance
“…The hybridization of polysomal poly(A)+-mRNA to 3 H-labeled single-copy DNA indicates a complexity which is about 75% of that observed for total polysomal RNA (i.e., 1.2 × 107 nucleotides, or 8900 different mRNAs). Thus, the mRNA population in T. cruzi is similar to that of several higher eukaryotic organisms [6,15,16,[26][27][28] in that it exhibits a distinct population of nonadenylated mRNAs (ca. 3000) which is not represented in the poly(A)+-mRNA class.…”
Section: Discussionmentioning
confidence: 99%
“…The hybridization of polysomal poly(A)+-mRNA to 3 H-labeled single-copy DNA indicates a complexity which is about 75% of that observed for total polysomal RNA (i.e., 1.2 × 107 nucleotides, or 8900 different mRNAs). Thus, the mRNA population in T. cruzi is similar to that of several higher eukaryotic organisms [6,15,16,[26][27][28] in that it exhibits a distinct population of nonadenylated mRNAs (ca. 3000) which is not represented in the poly(A)+-mRNA class.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of total mRNA in polysomes from a wide variety of cells appears to contain a 3'-terminal polyadenylic acid [poly(A)] segment (1,3,11,20). Among specific mRNA's, only histone mRNA in mammalian cells appears certain to arrive in the cytoplasm lacking poly(A) (1,3 found in the non-poly(A)+ [poly(A)-] fraction (10,32), whereas other studies suggest almost total overlap in sequence complexity (14) The cytoplasmic half-lives of the poly(A)+ mRNA's were established for each ofthe specific nine mRNA's and ranged from 3 h for the scarcest mRNA to 14 h. At least half of the total newly arrived mRNA molecules turn over considerably faster than 3 h, based on the rising percentage of the total represented by specific mRNA sequences.…”
mentioning
confidence: 99%
“…Grady et al [20] have shown that steady-state mouse liver and cultured fibroblast mRNA contains sequences found in either the poly(A)-containing pool or the poly(A)-free pool. They found only a small percentage of the sequence complexity existing in both of the two pools.…”
mentioning
confidence: 99%